LEGAL ISSUES OF ECONOMIC SUPPORT FOR PERSONAL SUBSIDIARY FARMS OF CITIZENS IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
This article addresses the legal challenges of providing economic support to personal subsidiary farms (PSFs) in the Republic of Kazakhstan. PSFs play a crucial role in the agricultural sector, contributing to food security and economic stability in rural areas. Despite their importance, private investment funds often encounter numerous issues, particularly in accessing economic support and legal protection. However, effective functioning and development of PSFs require economic stimulus measures and legal support. The article analyzes existing legal mechanisms of support, such as credit, subsidies, and preferential taxation, identifying shortcomings in their implementation. Attention is focused on legislative imperfections and practical challenges. Additionally, issues of PSF insurance and providing agricultural equipment through leasing as economic stimulus measures are discussed. The subject of the study is the legal mechanism of economic support for private farming of citizens in Kazakhstan. The conclusions underscore the significance of a comprehensive approach to legal regulation and economic support for PSFs in Kazakhstan, including legislative improvements, enhancement of financial mechanisms, and infrastructure development. The author provides recommendations for improving legal norms and implementing effective support mechanisms, which can contribute to enhancing the economic well-being of rural residents and the overall development of the agricultural sector. Keywords: personal subsidiary farms, economic support, legal issues, credit, subsidies, preferential taxation, Republic of Kazakhstan.